Nutrition literacy profile among adolescents in Kuwait: a cross-sectional study - AlBaloul, Anwar H.; AlKhalidi, Maraheb M.; AlAjmi, Haya (Frontiers in Public Health, 2024)
BackgroundAdolescent nutrition literacy and knowledge are associated with nutrient intake and obesity. With the rising prevalence of obesity in Kuwait, limited studies have assessed nutrition literacy among Kuwaiti adolescents. Therefore, this study aims to assess nutrition literacy among Kuwaiti adolescents and examine factors associated with nutrition literacy, such as body mass index (BMI) and dietary intake.MethodsA school-based cross-sectional study was conducted in public schools across Kuwait, enrolling a convenience sample of 375 adolescents (mean age = 15.6 years, 53.1% female participants). A self-administered questionnaire was used to collect relevant data. The Nutrition Literacy Assessment Instrument (NLit) score was used to assess nutrition knowledge and skills in making food choices.ResultsThe median NLit score among adolescents was 29 (IQR = 6). A large percentage (72.5%) of Kuwaiti adolescents demonstrated adequate overall nutrition literacy and scored adequately in the majority of NLit subscales. However, the majority of adolescents (73.3%) demonstrated inadequate nutrition literacy in understanding food labels. Predictors of NLit included BMI, place of residence, and smoking status. Moreover, the NLit score was negatively associated with the intake of sugar-sweetened beverages.ConclusionThis study’s findings may inform future research aimed at designing effective nutrition literacy interventions to enhance food choices among adolescents in Kuwait. The results of this study may also provide insights for policymakers and public health professionals to tailor food and nutrition programs to address the decline in food literacy skills and combat obesity.